Application and Importance of the International Assessment System in the Public Education System of the Republic of Uzbekistan - Ibodulloevna, Holova Sitora (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the improvement of the quality of education in the public education system, as well as the use of the internati onal assessment system and its significance.